Penerapan Sitem Informasi Akutansi Dengan Manfaatkan Teknologi Dalam Penyusunan Serta Pengelolahan Pembukuan Digital Pada UMKM - Dila Selvia (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The aim of writing this journal is to determine the application of digital-based accounting information systems in the bookkeeping of Small, Micro and Medium Enterprises (MSMEs), as well as understanding the importance of using digital technology for MSME players. By using case study methods from research and related journals, it shows that the implementation of accounting information systems by utilizing technology in MSMEs is currently starting to increase, as in MSME players who previously still used manual sales activities are now starting to utilize technology in sales and payment. However, MSMEs still prepare and manage accounting openings manually (traditionally) using paper. Counseling and training continues to be carried out so that it is hoped that the current rapid advances in technology can make it easier for MSMEs to carry out digital accounting which is more effective and efficient, and can also become MSMEs that are open to technological advances.